Spawning behaviour of a threatened Iberian cyprinid and its implications for conservation - Santos, Carla Sousa (2014)
This study presents the first ethological description of the reproductive behaviour of the cyprinid Squalius pyrenaicus, endemic to the Iberian Peninsula. The behavioural pattern of this endangered species during the breeding season is non-communal and includes the preparation of a spawning pit (depressions in the substratum) by males, a behaviour not described for Iberian cyprinids so far but already reported for North American cyprinids. The courting behaviour of males displaying in spawning pits has a strong signalling component towards females. Males from this species also showed agonistic behaviours against other males, related with the defence of their spawning pits. A positive association between male dominance and courtship activity is discussed, as well as the occurrence of sneaking by smaller and non-courting males. The implications of the described reproductive behaviours for the conservation and management of this endangered species are addressed.